2017
DOI: 10.1063/1.5001325
|View full text |Cite
|
Sign up to set email alerts
|

Improving estimation of kinetic parameters in dynamic force spectroscopy using cluster analysis

Abstract: Dynamic Force Spectroscopy (DFS) is a widely used technique to characterize the dissociation kinetics and interaction energy landscape of receptor-ligand complexes with single-molecule resolution. In an Atomic Force Microscope (AFM)-based DFS experiment, receptor-ligand complexes, sandwiched between an AFM tip and substrate, are ruptured at different stress rates by varying the speed at which the AFM-tip and substrate are pulled away from each other. The rupture events are grouped according to their pulling sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
(41 reference statements)
0
9
0
Order By: Relevance
“…The most probable unbinding force at the different loading rates were fit to the Bell-Evans model ( Bell, 1978 ; Evans and Ritchie, 1997 ) to measure the intrinsic off-rate under zero force, k 0 off and the width of energy barrier that inhibit protein dissociation, x β ( Figure 2A,B,C ). We used cluster analysis to group the single molecule unbinding events for fitting ( Yen and Sivasankar, 2018 ). We have previously shown that a K-means clustering algorithm greatly improves the estimation of kinetic parameters in DFS ( Yen and Sivasankar, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most probable unbinding force at the different loading rates were fit to the Bell-Evans model ( Bell, 1978 ; Evans and Ritchie, 1997 ) to measure the intrinsic off-rate under zero force, k 0 off and the width of energy barrier that inhibit protein dissociation, x β ( Figure 2A,B,C ). We used cluster analysis to group the single molecule unbinding events for fitting ( Yen and Sivasankar, 2018 ). We have previously shown that a K-means clustering algorithm greatly improves the estimation of kinetic parameters in DFS ( Yen and Sivasankar, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…We used cluster analysis to group the single molecule unbinding events for fitting ( Yen and Sivasankar, 2018 ). We have previously shown that a K-means clustering algorithm greatly improves the estimation of kinetic parameters in DFS ( Yen and Sivasankar, 2018 ). This analysis showed that the off-rate of Dsc2/Dsc2 dimers ( Figure 2A ) and Dsg2/Ecad dimers ( Figure 2C ) were comparable with a k 0 off of 1.26 s −1 and 1.24 s −1 respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 C-E) were calculated by multiplying the slope of the jump by the pulling velocity. k-means clustering was used to group the loading rates as described previously (70). Mean unbinding force and mean loading rate for the groups were fit using a weighted nonlinear least square fit to the Bell-Evans model (37).…”
Section: Methodsmentioning
confidence: 99%
“…Loading rates for the jump events used for dynamic force spectroscopy analysis ( Figure 4C-E) were calculated by multiplying the slope of the jump by the pulling velocity. K-means clustering was used to group the loading rates as described previously 64 . Mean unbinding force and mean loading rate for the groups were fit using a weighted non-linear least square fit to the Bell-Evans model 37 .…”
Section: Media Containing His-taggedmentioning
confidence: 99%